Studi Deskriptif Membaca tanpa Mengeja untuk Menstimulasi Kemampuan Literasi Anak Usia 5-6 Tahun: Descriptive Study of Reading Without Spelling to Stimulate Literacy Skill of Children Aged 5—6 Years - Harliana, Harliana (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study was conducted with the aim of describing reading activities without spelling to stimulate the literacy ability of children aged 5-6 years in TK Darma Wanita 20 Kembiritan. The study used a qualitative descriptive model. Data collection using observation techniques, interviews, and documentation studies. Data were analyzed during the study (on going process). From the results of the study, data were obtained that early literacy skills (reading) for early childhood using the method of reading without spelling are more efficient than conventional methods (spelling). The reading without spelling method helps students be able to read more complicated sentences within 6 months. This of course must be adjusted to the abilities of each student. So, it can be concluded that strategies in stimulating early childhood literacy skills can be successful if the methods used are in accordance with the characteristics of early childhood learning.